The Influence Of Job Engagement, Goal Orientation, And Career Satisfaction On Organizational Commitment At The Regional Staffing Agency Of The Province Of Kalimantan Timur - Agung Wicaksono; Djoko Setyadi; Doddy Adhimursandi (CV. AFDIFAL MAJU BERKAH, 2024)
This study explored the influence of job engagement, goal orientation, and career satisfaction on organizational commitment at the Regional Staffing Agency of Kalimantan Timur Province. Organizational commitment, which is essential for enhancing performance and trust in government agencies, is analyzed through three dimensions: affective, continuance, and normative commitment. This study utilizes a population of 71 civil servants from the Regional Staffing Agency and employs Structural Equation Modeling (SEM) through SmartPLS to analyze the relationships between variables. The study found that job engagement positively affects career satisfaction but has no significant direct impact on organizational commitment. Goal orientation had no significant influence on either career satisfaction or organizational commitment. Career satisfaction, although an important factor, does not directly impact organizational commitment. These findings highlight the complexities of the government’s work environment, where job security and rigid regulations may diminish the role of engagement and satisfaction in fostering commitment. The study concludes with recommendations for enhancing employee engagement and aligning organizational goals with personal aspirations to improve commitment and performance.